INVESTIGATION OF RISTOCETIN-INDUCED PLATELET AGGREGATION, PARAMETERS OF VON WILLEBRAND FACTOR AND THE COAGULATION FACTOR VIII AT ESSENTIAL ARTERIAL HYPERTENSION IN CHILDREN - M. V. Gomellya (Acta Biomedica Scientifica, 2014)
Ristocetin-induced platelet aggregation, von Willebrand factor and coagulation factor VIII of 170 children with essential arterial hypertension and 40 healthy children were investigated. Burdened hereditary thrombotic history, increase of ristocetin-induced platelet aggregation, activity and content of von Willebrand factor, very close to significant tendency to the increase of activity of coagulation factor VIII are typical for children with essential arterial hypertension with the increased risk of thrombosis.